Manifestações ototóxicas associadas ao uso de terapia anti - retroviral na infecção pelo HIV - Andreza Batista Cheloni Vieira (2006)
Otoneurologic manifestations in human immunodeficiency virus (HIV)-infected patients have been associated with highly active antiretroviral therapy (HAART), with frequency around 20%. This study, performed between July 2005 and July 2006, correlated otoneurologic alterations and HAART. It was evaluated 779 medical records of the HIV-infected patients followed in the Training and Reference Center inInfection and Parasitic Diseases Orestes Diniz (CRT-DIP/UFMG-PBH) to select the patients who were taking HAART and who were not taking this medication that would participate of this study. The inclusion criteria were: age above 18 years and to be in regular accompaniment and treatment. The exclusion criteria were: change of attendance service; lacks of data referring to the immunological profile and clinically unstable and/or interned patients. It was selected 162(57%) patients in use ofHAART (study group) and 122(43%) that were not in use of HAART (control group). Considering the selected participants, it was sent letter-invitation asking then to communicate with the researchers in case of dizziness, tinnitus, hearing loss or ear pain. Regarding the results, the groups were similar in relation to the sex; the mean age was 41.8 years for the group in use of HAART and 34.7 years for the group notin use of (P=0.00). The mean time of serologic confirmation was 80,3 months for the group in use of HAART and 39.3 for the group not in use of (P=0.00); CD4+ lymphocytes count was similar between the groups (P=0.60; OR=0.86; CI=0.52 1.43), the viral load was smaller in the group in use of HAART (P=0.00; OR=0.12; CI=0.06-0.25). Regarding the answer of the patients to the otoneurologic complaints, of the 284 sent letters, it was registered 21(7.4%) affirmative answers, being 14(8.6%) from the group in use of HAART and seven (5.8%) from the group not inuse of. Considering the 21 patients with complaints, hearing loss was the most important, with predominance in the group in use of HAART, with clinically significant difference between the groups (P=0.07). Concerning the definition of the otoneurologic diagnosis, 18 patients were submitted to clinical evaluation and specialized exams. Regarding the defined diagnoses, hearing loss induced by noise was observed in both groups similarly, earwax was more frequent in the group not inuse of HAART; three cases of idiopathic sensorioneural hearing loss and two cases of otosclerosis were observed in the group in use of HAART. It was verified that irreversible and otologic diseases related to hearing loss were more frequent in the group in use of HAART (P=0.05). Correlating the otoneurologics founds with the used HAART regimens, of 39, the associated with otoneurologic manifestations were: 1)didanosine + lamivudine+ lopinavir/r, 2) zidovudine+ lamivudine + efavirenz; 3) zidovudine + lamivudine + nevirapine; 4) stavudine + lamivudine + lopinavir/r and 5) didanosine + zidovudine + nelfinivir. The risk of ototoxicity associated with antiretroviral therapy seems to be real, but smaller than what has been reported in descriptive studies